Jejak Sejarah Surau Tinggi Calau dalam Perkembangan Pendidikan Islam di Sijunjuang - Sriwahyuni, Ilvi; Muhammad Kosim; Fauza Masyhudi; Zelly Riski Asrila Khalid (Jurnal Pendidikan Islam, 2025)
Surau Tinggi Calau is one of the relics of Islamic history that has a major contribution in the spread of Islam in Minangkabau, especially in Muaro Sijunjung nagari and its teachings are still being studied and practiced by the local community and people outside Sijunjung. This article aims to discuss three main aspects: the history of the establishment of Surau Tinggi Calau, the architectural form of Surau Tinggi Calau and the function of Surau Tinggi Calau in the development of Islamic education in Minangkabau. The method used in this research is a historical research method written in an analytical descriptive manner with steps or stages, namely: 1) Heuristics, 2) Source Criticism, 3) Interpretation, 4) Historiography. The results of this study indicate that Surau Tinggi Calau is one of the cultural heritages and Islamic history that has an important role in the development of education in Minangkabau, especially in Muaro Sijunjung nagari. The establishment of Surau Tinggi Calau is inseparable from the struggle of a great scholar named Sheikh Abdul Wahab around the 17th century. He taught Islam which was guided by the Syafi'i school of thought with the syattariyah tarekat school. Surau Tinggi Calau has a distinctive shape, at first glance this surau does not look like a house of worship in general, but this surau is in the form of a gadang house with a six-pitched roof, reflecting aesthetic values and local wisdom. This surau functions not only as a place of worship, but also as an Islamic educational institution and teaching center for the Syattariah order.